Rotinas de revisão no processo de geração e adoção de tecnologias na cafeicultura: estudos de casos - Bicalho, Ellenise Elsa Emídio (2011)
The project‟s object was to identify how the generation, diffusion and adoption process of agriculture machinery and equipments occur in the coffee production. In order to achieve this goal, a qualitative approach was chosen through a case study. The sector companies and coffee cooperative members were analyzed. The results showed that the technology innovation and generation process is accomplished, mainly by the company itself and through partnership with suppliers and clients. Research institutes, competitors or other institutions did not participated in the innovation and generation process. The main reason for innovative activity accomplished by the studied companies is the high level of competition in the sector. Another factor considered important was the accomplishment of the consumer‟s necessities and wishes. It was observed that the best way of innovation diffusion take place in the participation of events and fairs. The client‟s properties products testing is another way used in the innovation diffusion. By the farmer‟s side, the diffusion takes place through the direct and personal information trade. Among the coffee growers studied, the technology diffusion takes place, many times, by the cooperative, through conferences offered to them. The adoption process meets several challenges to be overdone, but two factors can be outstanding: The labor cost and sales coffee price. These two factors are crucial for the grower makingdecision.